The Year of the Salmonella Seekers-1977 - J.R.L Forsyth; N.McK. Bennett; S. Hogben; E.M.S Hutchinson; G. Rouch; A. Tan; J. Taplin (Elsevier, 2003)
Abstract In 1977 two major outbreaks of salmonella infection originated in Victoria. The first of these, involving Salmonella Bredeney, continued over some seven months and was traced to contamination of powdered milk‐based infant formulae during manufacture. This caused cases of gastroenteritis among young children throughout Australia. Another incident led to the discovery that salmonella serovars were colonising not one, but a number of dairy factories through the State. The second outbreak was of typhoid, stemming from a carrier working in a sandwich bar, and occurred during the course of the first, almost overwhelming public health resources and delaying investigation of the first outbreak. The background, recognition, course, investigation and resolution of these, previously unpublished, outbreaks are described, drawing upon the experiences of authors involved at the clinical, public health and laboratory levels, and preserved, contemporary records. Taken together, these outbreaks directly stimulated radical improvements in the construction and management of dairy factories in the State; initiated the adoption of risk management concepts in food factories; caused the launch of regional regulations compelling notification of salmonellas found in food manufacture; and led to the setting‐up of an enhanced national, laboratory‐based system for the collection, analysis and dissemination of information on enteric pathogens.